HTML5 solutions essential techniques for HTML5 developers - Casario, Marco (Apress, 2011)
HTML5 brings the biggest changes that HTML has seen in years. Web designers and developers now have a whole host of new techniques up their sleeves, from displaying video and audio natively in HTML, to creating realtime graphics directly on a web page without the need for a plugin. But all of these new technologies bring more tags to learn and more avenues for things to go wrong. HTML5 Solutions provides a collection of solutions to all of the most common HTML5 problems. Every solution contains sample code that is production-ready and can be applied to any project.